The last room on the left - Konen, Leah (G.P. Putnam's Sons, 2025)
Kerry's life is in shambles: Her husband has left her, her drinking habit has officially become a problem, and though the deadline for her big book deal--the one that was supposed to change everything--is looming, she can't write a word. When she sees an ad for a caretaker position at a revitalized roadside motel in the Catskills, she jumps at the chance. It's the perfect getaway to finish her book and start fresh. But as she hunkers down in a blizzard, she spots something through the window: a pale arm peeking out from a heap of snow. Trapped in the mountains and alone with a dead, frozen body, Kerry must keep her head and make it out before the killer comes for her too. But is the deadly game of cat-and-mouse all in her mind? The body count begs to differ…"--